TAXONOMIC KEY FOR THE IDENTIFICATION OF VIRTUAL SHELLS OF MARINE GASTROPODS OF THE CUBAN FAUNA - Armiñana-García, Rafael (2022)
ABSTRACT Dichotomous keys are resources or tools that researchers, teachers or other personnel linked to the study of biological sciences use for the determination of different species of organisms, through the comparison of two excluding characters. The objective of the research presented is aimed at making a dichotomous key in electronic format for the identification of virtual shells of marine gastropods present in the malacological fauna of Cuba, and in correspondence with the teaching-learning process of General Zoology I, in the career of Bachelor in Education. Biology, at the Central University "Marta Abreu" of Las Villas, Villa Clara, Cuba. In the research, different methods were used to collect information and process it in its dialectic interrelation, which allowed identifying the detected insufficiencies and formulating the solution. The information for the diagnosis is obtained from the application of different methods, such as document review, participant observation, student survey and evaluation by expert criteria. To mitigate the problems detected, and with a view to introducing for the first time the dichotomous keys in digital format, for the identification of virtual shells of marine gastropods, in the degree course in Biology Education, these are elaborated, which were subjected to expert criteria that evaluated them as relevant, before being implemented in the course 2020-2021, with excellent results. Key words: dichotomous key – gastropod – mollusk – shell – Zoology